2011
DOI: 10.1017/s0022149x11000757
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation amongClonorchis sinensisisolates from different geographic regions in China revealed by sequence analyses of four mitochondrial genes

Abstract: The present study examined sequence variation in four mitochondrial (mt) genes, namely cytochrome c oxidase subunits 1 (cox1) and 2 (cox2), and NADH dehydrogenase subunits 1 and 2 (nad1 and nad2) among Clonorchis sinensis isolates from different endemic regions in China, and their phylogenetic relationships with other zoonotic trematodes were reconstructed. A portion of the cox1 and cox2 genes (pcox1 and pcox2), and nad1 and nad2 genes (pnad1 and pnad2) were amplified separately from individual liver flukes by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…However, high inter-specific sequence differences were observed between D. dendriticum and some common trematodes (Figure 1), with 24.74 -29.40% for pcox1, 33.25 -49.40% for pnad1 and 29.07 -39.48% for pcytb. These results were consistent with the results of other helminthes in previous studies, including trematodes and cestodes (Li et al 2008;Liu et al 2012;Wang et al 2012Wang et al , 2013.…”
Section: Genbank Accession Numbersupporting
confidence: 95%
See 1 more Smart Citation
“…However, high inter-specific sequence differences were observed between D. dendriticum and some common trematodes (Figure 1), with 24.74 -29.40% for pcox1, 33.25 -49.40% for pnad1 and 29.07 -39.48% for pcytb. These results were consistent with the results of other helminthes in previous studies, including trematodes and cestodes (Li et al 2008;Liu et al 2012;Wang et al 2012Wang et al , 2013.…”
Section: Genbank Accession Numbersupporting
confidence: 95%
“…In comparison with rDNA, mtDNA is more suitable to study genetic differences among individuals or populations within a species of nematode, trematode and cestode, due to maternal inheritance, rapid evolutionary rate and higher mutation rates of mtDNA (Le et al 2002;Gasser et al 2008;Lin et al 2012;Liu et al 2012;Ma et al 2012). Zhao et al (2009) suggested that NADH dehydrogenase subunits 5 (nad5), cytochrome c oxidase subunit 3 and 4 (cox3 and cox4) genes would be new and useful markers for studying the inter-and intra-population genetic variations of Schistosoma japonicum.…”
Section: Introductionmentioning
confidence: 99%
“…The CsM33 marker is the most polymorphic (11 alleles), while CsM26 had only 2 alleles. Variation of microsatellites in our study mainly differ in the repeat numbers while other genetic markers, such as rDNA or mtDNA, the difference is in its sequence (Lee and Huh 2004; Liu et al 2012; Xiao et al 2013). …”
Section: Discussionmentioning
confidence: 64%
“…Infection with this liver fluke can lead to several hepatobiliary diseases including cholangiocarcinoma as it is classified as a Group I carcinogen by the International Agency for Research on Cancer, WHO (Bouvard et al 2009; Hong and Fang 2012). Since the parasite is distributed over a half of Asia, genetic diversity in the endemic regions has been reported using conventional molecular markers such as mtDNA and rRNA (Lee and Huh 2004; Liu et al 2012; Park 2007; Tatonova et al 2012; Tatonova et al 2013; Xiao et al 2013). These genetic variations of C. sinensis may influence disease presentation, host specificity and other biological functions (Choi 1984; Saijuntha et al 2007; Hong and Fang 2012; Sun et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…DNA markers similar to the ones used in our work have been extensively tested over the past ten years to establish the population structure and phylogeography of human-infecting trematodes from Europe [40,41], Eastern and South-Eastern Asia [42,51,77,78], Africa [27,30] and America [41]. However, to our knowledge no such analysis of trematode species inhabiting both Northern Asia and Eastern Europe was done.…”
Section: Low Genetic Diversity and Pronounced Star-like Haplotype Netmentioning
confidence: 99%